Integration Of Special Ministry Management And Leadership Theology In Improving The Effectiveness And Ethics Of Ministry In The Church - Djumari, Brigita; Kalalo, Jefry (Peneliti.net, 2025)
This study examines the application of management theology in church ministry with a focus on special ministers as spiritual leaders as well as administrative in the Evangelical Church in Minahasa (GMIM). This research aims to explore how the principles of management theology can be applied contextually to improve the performance of church ministry while strengthening the integrity of special ministers. This study uses a qualitative approach with descriptive methods and phenomenological analysis. The results of the study show that the application of management theology that is integrated with Christian values and the contextualization of local culture is able to increase the effectiveness of ministry, especially in the management of church resources and strategic decision-making. An ethics of service based on love, justice, and integrity is an important foundation in building the congregation's trust in the leadership of the church. The application of principles such as strategic planning, stewardship-based resource management, and transformational leadership allows the church to carry out its mission more holistically and relevant to the challenges of the times. This research makes a new contribution by offering a model of application of management theology that is holistic, adaptive, and responsive to the dynamics of contemporary ecclesiastical ministry. Thus, management theology is not only a tool of administrative management, but also a means of spiritual and social transformation that strengthens the role of the church as an agent of change in society.